Efektivitas Penerapan Scaffolding terhadap Self Efficacy Mahasiswa pada Mata Kuliah Matematika Ekonomi di Program Studi Pendidikan Ekonomi STKIP Kumala Lampung - Nofiansyah, Wahyu (Institut Agama Islam Negeri Curup, 2021)
The problem in this study is that students' self efficacy is still lacking in the learning process which has an impact on the final value of the economic mathematics course. This study aims to determine the effectiveness of the application of scaffolding on student self efficacy in the economic mathematics course of STKIP Kumala Lampung Metro. This research is an experimental research with one group pretest-posttest design. The population in this study were all students of Economic Education in the fourth semester of the 2020/2021 academic year, while the sample consisted of 30 students. The sampling technique used is saturated sampling. The data collection technique was done by using a questionnaire. In this study, prerequisite tests and data analysis processes, both from normality tests and hypothesis testing, use the help of SPSS data processing applications. The results obtained that the distribution is normal, then the t-test with a sig level of 5% obtained the results thitung (3,161) > ttabel (2,045) which means there is a difference between before and after the application of scaffolding on students' self efficacy. Furthermore, for the effect size test results obtained 0.577 which means it is included in the medium category. So it can be concluded that there is an effectiveness of the application of scaffolding on the self efficacy of students in the economics mathematics course.